Smoking is associated with adrenal adenomas and adrenocortical carcinomas: a nationwide multicenter analysis. (2020) - Yousaf, Ahmed; Patterson, Jessica; Hobbs, Gerald; Davis, Stephen M.; Yousaf, Muhammad; Hafez, Maria; Albandar, Heidar; Hogan, Thomas; Kolodney, Joanna
Highlights: Smoking has been suggested as a risk factor for adrenal cortical carcinoma. Tobacco use is associated with significant increases in adrenal adenoma and ACC in two population-level databases. Currently, risk factors for adrenal carcinogenesis is limited. Our findings support the association of tobacco use with adrenal adenomas and adrenal cortical carcinoma. Abstract: Microabstract: The effect of smoking on adrenal cancer is poorly understood. A clear association of adrenal adenoma and adrenocortical carcinoma with smoking among the United States population is observed. This association points to the possibility of environmental carcinogenic and/or lifestyle factors contributing to adrenal cancer formation. Our results support the association of tobacco use with adrenal adenomas and adrenal cortical carcinoma. Background: Smoking has been suggested as a risk factor for adrenal cortical carcinoma (ACC), but this hypothesis has only been inferred from a single study using all types of adrenal cancers including pheochromocytoma, neuroblastoma, as well as ACC. Given the high rate of tobacco use in West Virginia, we hypothesized that smoking might contribute to increased prevalence of ACC. Materials and Methods: De-identified institutional review board-exempted records were analyzed in the Surveillance, Epidemiology, and End Results (SEER) Program from 2001-2016 and in patients from the United States nationwide, multicenter TriNetX database of 41, 063, 707 patients from 2008-2018. In addition, the state-level ratio of smoking to ACC prevalence was computed in all 50 states using data from SEER and the Center for Disease Control. West Virginia Health System data from 2008-2018 was extracted to confirm population-level findings. Melanoma was used as a cancer control in both databases. Results: 6, 946 ACC cases were identified. West Virginia had the highest smoking rate and the second highest rate of ACC. A significant association was found between smoking and ACC (Pearson correlation coefficient r = 0.4887, p=.0004). From 2008 to 2018 using TriNetX, 846 ACC and 36, 434 AA were extracted. Both adrenal neoplasm cohorts had increased prevalence of tobacco use compared with melanoma controls, where 23.5% were smokers compared to 36.4% and 33.9% in the ACC and AA groups, respectively (p<0.0001 each). Conclusion: To our knowledge, this is the first United States population-based study supporting smoking as a risk factor for adrenal carcinogenesis and ACC.